Maqâshid Syarî’ah Perception Toward Letter of Credit as Export-Import Risk Mitigation at Indonesian Fishery Trade Experience - Imam Kamaluddin; Eka Risana Putri; Setiawan bin Lahuri; Suyoto Arief (Universitas Darussalam Gontor, 2021)
Export-Import is one of the engines that drive economic growth. Compared to domestic trade, Export-Import trade or international trade contains more risks. In reducing the risks that may occur in international trade, exporters use Letters of Credit as a guarantee of payment for goods. Compared with the weaknesses and benefits of using a Letter of Credit (LoC) in risk mitigation in export-import transactions, the benefits of using it are greater. Therefore, this study aims to find out how to use a Letter of Credit (LoC) as an instrument in mitigating export-import risk based on the maqâshid syarî’ah‎ review. This research is qualitative with observation, interviews, and documentation in data collection. The data is analyzed from the data obtained from the object of the research is a descriptive analysis using the maqâshid syarî’ah‎ approach by looking at the risks that may occur in the use of a Letter of Credit (LoC). The results of the study stated that the use of a Letter of Credit (LoC) as an export-import payment instrument is allowed if it becomes a necessity and creates benefits for the wider community. Providing facilities for issuing and using letters of credit as export and import documents needs to be developed so that it will increase exporters' interest and encourage an increase in export-import, as well as an increase in the value of foreign exchange, besides that it is necessary to develop Islamic banks as providers of shari’ah letter of credit services for exporters and Muslim importer.